KONSEP ANALISIS LOKASI FASILITAS JARINGANPENGELOLAAN LIMBAH KOTA - Setya Murdapa, Petrus (Widya Warta, 2020)
Ground  water  is  actually  a  source  of  clean  water.  As  a  source,  it  should  not  be  polluted  by wastewater. However, as the population grows, the discharge of wastewater will also increase. Municipal  wastewater  must  bespecifically  managed  so  that  its  disposal  does  not  mix  with groundwater  by  providing  a  special  pipeline  to  drain  and  collect  municipal  wastewater  to collection   and   processing   facilities,   before   finally   being   discharged   into   rivers   or   the environment afterconditions are safe. This wastewater treatment pipeline network resembles a commodity distribution network from industry to consumers. By analogy and adjustment, the maximum covering solution method can be used to design the location of the facility and the waste treatment plant. The goal is to obtain the lowest possible length of pipe, which covers all municipal  wastewater  sources,  namely  settlements  and  other  public  facilities.  The  analysis must  be  carried  out  in  two  stages,  which  in  this  paper  are  called  level-1  and  level-2.  In  this paper, only the basic concepts of the study are revealed. Simple case examples and numerical solutions are briefly revealed